Conductive paste and preparation method thereof, TOPCon cell and preparation method thereof
Patent Information
- Application Number
- CN202611229829.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2026-05-14
- Filing Date
- 2026-08-13
- Publication Date
- 2026-10-23
AI Technical Summary
然而,单一铅系玻璃粉在醋酸环境中易发生铅离子溶出,导致玻璃网络破坏,耐酸性较差;单一铋系玻璃粉虽然环境友好,但其玻璃网络结构相对疏松,对助焊剂和氯化钠的阻挡能力不足
[0007]与现有技术相比,本申请提供的导电浆料的原料包括银导电材料、有机载体、玻璃粉以及界面强化助剂。
Smart Images

Figure CN122968033A_ABST
Abstract
Description
[0001] This disclosure claims priority to Chinese patent application No. 202610666634.3, filed on May 14, 2026, entitled "A Conductive Paste and its Preparation Method, TOPCon Battery and its Preparation Method", the entire contents of which are incorporated herein by reference. Technical Field
[0002] This application relates to the field of electronic materials and component processing technology, and in particular to a conductive paste and its preparation method, and a TOPCon battery and its preparation method. Background Technology
[0003] Solar cells are devices that convert sunlight into electrical energy. To collect more sunlight and reduce light shading by the front conductive electrodes, ultra-fine lines are increasingly used for the front grid. These ultra-fine lines not only place higher demands on the printing performance of the conductive paste but also on the reliability of the front grid. Before being laminated into modules, solar cells require welding, during which the grid is corroded by the soldering flux. During manual module handling, sweat containing sodium chloride can also corrode the grid. After the solar cells are manufactured into modules, they are exposed to outdoor environments for extended periods. The ethylene-vinyl acetate copolymer used as the module encapsulation material decomposes to produce acetic acid, which corrodes the cell's grid.
[0004] In existing technologies, the front conductive paste of tunnel oxide passivated contact (TOPCon) batteries typically uses lead-containing or bismuth-containing glass powder as a sintering aid to promote ohmic contact between silver powder and the silicon substrate. However, lead-based glass powder is prone to lead ion dissolution in acetic acid environments, leading to glass network damage and poor acid resistance; while bismuth-based glass powder, although environmentally friendly, has a relatively loose glass network structure, resulting in insufficient resistance to flux and sodium chloride. Furthermore, traditional glass powder systems lack effective network-strengthening components, making it difficult to achieve both good ohmic contact and long-term corrosion resistance under ultra-fine grid line conditions. Summary of the Invention
[0005] This application is made in view of the above-mentioned issues.
[0006] According to one aspect of this application, a conductive paste is provided, the raw materials of which include: The conductive paste contains silver conductive material, an organic carrier, glass powder, and an interface strengthening agent. Based on the mass fraction of the conductive paste, the silver conductive material comprises 87 to 92 parts, the organic carrier comprises 7 to 10 parts, and the glass powder and interface strengthening agent comprise 1 to 5 parts. The glass powder comprises a lead-bismuth oxide component, an iron-titanium oxide component, and an auxiliary glass-forming component. Based on the mass fractions of the glass powder, the lead-bismuth oxide component comprises 30 to 50 parts, the iron-titanium oxide component comprises 2 to 10 parts, and the auxiliary glass-forming component comprises 40 to 68 parts.
[0007] Compared with the prior art, the conductive paste provided in this application includes silver conductive material, organic carrier, glass powder and interface strengthening agent as raw materials.
[0008] First, based on the mass fraction of the conductive paste, the silver conductive material provided in this application is 87 to 92 parts. This parameter range ensures that a continuous silver conductive network is formed after the paste is cured, thereby obtaining a low volume resistivity and good ohmic contact performance.
[0009] Secondly, the organic carrier provided in this application is in the form of 7 to 10 parts, which can provide suitable viscosity and rheological properties for the slurry, enabling it to be applied to the front grid of the TOPCon battery by screen printing, forming uniform and fine grid lines and reducing light loss.
[0010] Furthermore, the glass powder provided in this application includes a lead-bismuth oxide component, an iron-titanium oxide component, and an auxiliary glass-forming body component. The lead-bismuth oxide component comprises 30 to 50 parts by mass of the glass powder. Under the combined action of lead and bismuth oxides, a complementary dual network can be formed in the glass network, reducing the amount of non-bridging oxygen and making the glass phase more compact. The iron-titanium oxide component comprises 2 to 10 parts, capable of forming Fe-O-Ti bonds and enhancing the connectivity of the glass network. The auxiliary glass-forming body component comprises 40 to 68 parts. This component serves as the main framework of the glass powder, providing a matrix for the distribution and embedding of the lead-bismuth oxide and iron-titanium oxide components, and synergistically forming a complete glass network with them. During sintering, it assists in the flow and spreading of the glass phase, thereby ensuring the normal functioning of the lead-bismuth dual network and the iron-titanium synergistic strengthening mechanism. It is evident that the synergistic effect of the lead-bismuth oxide component, the iron-titanium oxide component, and the auxiliary glass-forming component enhances the chemical stability of the glass phase, thereby effectively resisting corrosion from acetic acid, organic acids in the flux, and sodium chloride solution. Therefore, the electrode formed from this slurry exhibits resistance to acetic acid, flux corrosion, and NaCl corrosion.
[0011] Furthermore, the interface strengthening agent provided in this application can react with the silicon substrate during sintering to form a stable interface layer, reducing contact resistance and further blocking the penetration of corrosive media, thus enabling the conductive paste to possess more reliable interface performance during use. Based on this, this application limits the total amount of glass powder and interface strengthening agent to 1 to 5 parts. Within this parameter range, the amount of non-conductive components added can be kept low, thereby reducing the dilution and blocking effects on the continuous network of the silver conductive material, which is beneficial for maintaining low bulk resistivity and good conductivity. At the same time, glass powder and interface strengthening agent can play their roles as sintering aids and interface modifiers with minimal dosage, avoiding adverse phenomena such as glass phase floating or excessively thick interfaces caused by excessive addition. Moreover, controlling the total addition amount to less than 5 parts while ensuring functional achievement can further reduce paste production costs and reduce unnecessary erosion of the silicon substrate.
[0012] In summary, the combined effect of the aforementioned materials and their dosages significantly improves the electrodes' resistance to acetic acid, flux, and sodium chloride corrosion while ensuring high conductivity, good printability, and low additive content, thereby enhancing the long-term reliability of TOPCon battery modules.
[0013] According to another aspect of this application, a method for preparing a conductive paste is also provided, comprising: A premixed material is obtained by mixing 1 to 5 parts by weight of glass powder and interface strengthening agent, 87 to 92 parts by weight of silver conductive material and 7 to 10 parts by weight of organic carrier. The premixed materials are dispersed evenly by three-roll milling to obtain a conductive slurry.
[0014] According to another aspect of this application, a method for preparing a TOPCon battery is also provided, comprising: The conductive paste described above is applied to the front electrode area of the TOPCon battery by screen printing. After printing, a fine grid pattern is formed, resulting in a battery cell with a wet paste grid on the surface. The battery cells are sequentially subjected to sintering, light injection, and laser-assisted sintering to form TOPCon batteries.
[0015] According to another aspect of this application, a TOPCon battery is also provided, comprising: prepared by the above-described method for preparing a TOPCon battery.
[0016] Compared with the prior art, the beneficial effects of the conductive paste preparation method, TOPCon battery and preparation method provided in this application are the same as the beneficial effects of the conductive paste provided in this application, and will not be repeated here.
[0017] It should be understood that both the foregoing general description and the following detailed description are exemplary and intended to provide further illustration of the claimed technology. Attached Figure Description
[0018] The above and other objects, features, and advantages of this application will become more apparent from the more detailed description of the embodiments of this application in conjunction with the accompanying drawings. The accompanying drawings are used to provide a further understanding of the embodiments of this application and form part of the specification. They are used together with the embodiments of this application to explain this application and do not constitute a limitation thereof. In the accompanying drawings, the same reference numerals generally represent the same components or steps.
[0019] Figure 1 A flowchart illustrating the preparation method of conductive paste according to an embodiment of this application is shown; Figure 2 A flowchart illustrating the fabrication method of the TOPCon battery according to an embodiment of this application is shown; Figures 3 to 10 Images of electroluminescence tests acquired after flux experiments of solar cells made from the conductive pastes obtained in Examples 6 to 10 and Comparative Examples 4 to 6 of this application are shown in sequence. Detailed Implementation
[0020] To make the objectives, technical solutions, and advantages of this application more apparent, exemplary embodiments according to this application will be described in detail below with reference to the accompanying drawings. Obviously, the described embodiments are merely some embodiments of this application, and not all embodiments of this application. It should be understood that this application is not limited to the exemplary embodiments described herein.
[0021] Solar cells are devices that convert sunlight into electrical energy. To collect more sunlight and reduce light shading by the front conductive electrodes, ultra-fine lines are increasingly used for the front grid. These ultra-fine lines not only place higher demands on the printing performance of the conductive paste but also on the reliability of the front grid. Before being laminated into modules, solar cells require welding, during which the grid is corroded by the soldering flux. During manual module handling, sweat containing sodium chloride can also corrode the grid. After the solar cells are manufactured into modules, they are exposed to outdoor environments for extended periods. The ethylene-vinyl acetate copolymer used as the module encapsulation material decomposes to produce acetic acid, which corrodes the cell's grid.
[0022] In existing technologies, the front conductive paste of tunnel oxide passivated contact (TOPCon) batteries typically uses lead-containing or bismuth-containing glass powder as a sintering aid to promote ohmic contact between silver powder and the silicon substrate. However, lead-based glass powder is prone to lead ion dissolution in acetic acid environments, leading to glass network damage and poor acid resistance; while bismuth-based glass powder, although environmentally friendly, has a relatively loose glass network structure, resulting in insufficient resistance to flux and sodium chloride. Furthermore, traditional glass powder systems lack effective network-strengthening components, making it difficult to achieve both good ohmic contact and long-term corrosion resistance under ultra-fine grid line conditions.
[0023] To address the aforementioned problems, this application provides a conductive paste that significantly improves the electrodes' resistance to acetic acid, flux, and sodium chloride corrosion while maintaining high conductivity, good printability, and low additive dosage, thereby enhancing the long-term reliability of TOPCon battery modules. The raw materials of this conductive paste include: The mixture comprises silver conductive material, organic carrier, glass powder, and interface strengthening agent; by mass parts of the conductive paste, the silver conductive material comprises 87 to 92 parts, the organic carrier comprises 7 to 10 parts, and the total proportion of glass powder and interface strengthening agent comprises 1 to 5 parts; the glass powder includes lead-bismuth oxide component, iron-titanium oxide component, and auxiliary glass forming component, by mass parts of the glass powder, the lead-bismuth oxide component comprises 30 to 50 parts, the iron-titanium oxide component comprises 2 to 10 parts, and the auxiliary glass forming component comprises 40 to 68 parts.
[0024] Understandably, 87-92 parts by weight of silver conductive material ensures the formation of a continuous silver conductive network after the slurry cures, resulting in low bulk resistivity and good ohmic contact performance. Secondly, 7-10 parts by weight of organic carrier provides suitable viscosity and rheological properties for the slurry, allowing it to be screen-printed onto the front grid of the TOPCon cell, forming uniform and fine grid lines and reducing light-blocking losses. Thirdly, based on the mass percentage of glass powder, 30-50 parts by weight of lead-bismuth oxide can form a structurally complementary dual network within the glass network, reducing the amount of non-bridging oxygen and making the glass phase more compact. 2-10 parts by weight of iron-titanium oxide can form Fe-O-Ti bonds, enhancing the connectivity of the glass network. Meanwhile, the auxiliary glass-forming component, comprising 40 to 68 parts by weight, serves as the main framework of the glass powder, providing a matrix for the distribution and embedding of the lead-bismuth oxide and iron-titanium oxide components. It synergistically forms a complete glass network with these components, assisting in the flow and spreading of the glass phase during sintering, thus ensuring the proper functioning of the lead-bismuth dual network and the iron-titanium synergistic strengthening mechanism. It is evident that the synergistic effect of the lead-bismuth oxide, iron-titanium oxide, and auxiliary glass-forming component results in higher chemical stability of the glass phase, effectively resisting corrosion from acetic acid, organic acids in flux, and sodium chloride solution. Therefore, the electrode formed from this slurry exhibits resistance to acetic acid, flux corrosion, and NaCl corrosion.
[0025] Furthermore, the interface strengthening agent provided in this application can react with the silicon substrate during sintering to form a stable interface layer, reducing contact resistance and further blocking the penetration of corrosive media, thus enabling the conductive paste to possess more reliable interface performance during use. Based on this, this application limits the total amount of glass powder and interface strengthening agent to 1 to 5 parts. Within this parameter range, the amount of non-conductive components added can be kept low, thereby reducing the dilution and blocking effects on the continuous network of the silver conductive material, which is beneficial for maintaining low bulk resistivity and good conductivity. At the same time, glass powder and interface strengthening agent can play their roles as sintering aids and interface modifiers with minimal dosage, avoiding adverse phenomena such as glass phase floating or excessively thick interfaces caused by excessive addition. Moreover, while ensuring functional achievement, controlling the total addition amount to less than 3 parts can further reduce the paste production cost and reduce unnecessary erosion of the silicon substrate.
[0026] In one alternative embodiment, the lead-bismuth oxide component of this application includes lead oxide and bismuth oxide, and the iron-titanium oxide component includes iron oxide and titanium oxide.
[0027] For example, based on the mass parts of glass powder, the amount of lead oxide in this application embodiment is 10 to 40 parts, the amount of bismuth oxide is 5 to 30 parts, the amount of iron oxide is 1 to 9 parts, and the amount of titanium oxide is 1 to 5 parts.
[0028] Due to the differences in ionic radius and charge density between lead and bismuth ions, the high charge density of bismuth ions in 5-30 parts by mass of bismuth oxide enhances the bonding strength with oxygen ions, while lead ions in 10-40 parts by mass of lead oxide provide charge compensation, thereby reducing the amount of non-bridging oxygen and making the glass network more complete and dense. Secondly, iron ions in 1-9 parts by mass of iron oxide and titanium ions in 1-5 parts by mass of titanium oxide tend to form Fe-O-Ti bonds. This bonding method enhances the three-dimensional connectivity of the glass network, with iron ions mainly playing a charge compensation role and titanium ions acting as a network strengthening agent. Their synergistic effect further improves the chemical stability of the glass phase. In summary, the combination of these four oxides results in a glass phase formed after sintering with glass powder exhibiting lower corrosive media permeability, thus more effectively resisting the corrosion of acetic acid, flux, and sodium chloride.
[0029] In one optional embodiment, the auxiliary glass-forming component of this application includes a primary glass-forming component and a secondary glass phase component. The primary glass-forming component includes boron oxide, silicon oxide, and aluminum oxide, wherein, based on the mass parts of the glass powder, the amount of boron oxide is 30 to 60 parts, the amount of silicon oxide is 0.5 to 5 parts, the amount of aluminum oxide is 5 to 15 parts, and the amount of the secondary glass phase component is 0 to 5 parts.
[0030] Among them, boron oxide, at a mass fraction of 30 to 60 parts, can form a stable boron-oxygen tetrahedral network, providing the main framework for the glass phase. Silicon oxide, at a mass fraction of 0.5 to 5 parts, also acts as a network former, improving the polymerization degree and chemical corrosion resistance of the glass network. Alumina, at a mass fraction of 5 to 15 parts, enters the network as an intermediate, filling structural voids and enhancing network density. Through the combined action of these three oxides, the softening temperature, viscosity, and coefficient of thermal expansion of the glass powder can be effectively adjusted, ensuring suitable flowability and wettability during sintering.
[0031] In addition, minor glass phase components in the range of 0 to 5 parts by mass can further fine-tune the physicochemical properties of the glass, for example, by changing the interfacial reactivity or improving the resistance to crystallization.
[0032] Based on this, the formulation design of the above-mentioned auxiliary glass forming components can enable glass powder to form a complete and stable glass network structure even at a low addition amount, thereby providing good matrix conditions for the synergistic strengthening of lead-bismuth oxide components and iron-titanium oxide components.
[0033] For example, the secondary glass phase components in this application embodiment include one or more of tungsten oxide, cobalt oxide, gallium oxide, and chromium oxide. These transition metal oxides can play a fine-tuning and reinforcing role in the glass network, making the overall glass structure more uniform and dense, while working together with the main components in the glass powder to improve chemical stability. Because they can function at a low addition ratio, they do not damage the original glass network or affect the conductive pathways. Furthermore, these oxides can further enhance the electrode's resistance to corrosive media such as acetic acid, sodium chloride, and flux, thereby enabling the battery to maintain a more stable power generation efficiency during long-term use.
[0034] In one alternative embodiment, based on the mass fraction of the conductive paste, the amount of glass powder in this application embodiment is 1 to 4 parts, and the amount of interface strengthening agent is greater than 0 and less than or equal to 1 part. For example, the amount of glass powder in this application embodiment is 1, 2, or 4 parts, and the amount of interface strengthening agent is 0.5 or 1 part. Within the above parameter range, the glass powder can form a dense glass network during sintering, while the interface strengthening agent can react with the silicon substrate to generate a thin layer of metal silicide or oxide at the silver-silicon interface, thereby reducing contact resistance and enhancing interfacial bonding strength. Furthermore, since the amount of interface strengthening agent added is low, it does not significantly dilute the silver conductive network while improving interfacial contact, thus improving the corrosion resistance of the electrode while maintaining good conductivity.
[0035] In a preferred embodiment, based on the mass fraction of the conductive paste, the glass powder in this application embodiment is preferably 2 to 4 parts, more preferably 2 to 3 parts; the interface strengthening agent is preferably greater than 0 and less than or equal to 0.8 parts, more preferably greater than 0 and less than or equal to 0.5 parts. Within this parameter range, the effect is best.
[0036] For example, the interface strengthening agent in this application embodiment includes one or more of aluminum powder, silicon powder, aluminum-silicon alloy powder, and alumina powder. The alumina or silicon oxide formed by the partial oxidation of aluminum or silicon powder during sintering can fuse with the glass network, further improving the density and chemical stability of the glass phase. Alumina powder, as a directly added stabilizing oxide, can adjust the viscosity and coefficient of thermal expansion of the glass, preventing excessively thick interfaces or glass phase floating.
[0037] In one optional embodiment, the average particle size D50 of the silver conductive material in this application embodiment is 0.5~2μm, and the maximum particle size D100 of the silver conductive material is greater than 0 and less than or equal to 4μm. The smaller silver powder particles can increase the specific surface area during sintering, promoting the interconnection between silver particles and between silver and the silicon substrate, thereby forming a continuous and dense conductive network, which helps to reduce the bulk resistivity and contact resistance of the electrodes. Simultaneously, limiting the maximum particle size to within 4 micrometers can effectively prevent individual large particles from clogging the mesh or causing grid line breakage during screen printing, ensuring the continuity and uniformity of the fine grid lines. Furthermore, the uniform particle size distribution also contributes to the stable dispersion of silver powder in the paste, reducing sedimentation and thus improving the storage stability and printing consistency of the paste.
[0038] In one alternative embodiment, the average particle size D50 of the glass powder in this application embodiment is greater than 0 and less than or equal to 1.5 μm, and the maximum particle size D100 of the glass powder is greater than 0 and less than or equal to 4 μm.
[0039] Within the aforementioned parameter range, smaller glass powder particles have a higher specific surface area, allowing them to soften and flow more quickly during sintering. This results in a uniform and thin glass layer between the silver powder and the silicon substrate, ensuring effective penetration of the passivation layer while preventing excessively thick glass phases from hindering conductive contact. Simultaneously, strict control of the maximum particle size prevents glass powder from clogging the mesh during screen printing, ensuring the integrity and continuity of the ultrafine grid lines.
[0040] In one alternative embodiment, the average particle size D50 of the interface strengthening agent in this application embodiment is greater than 0 and less than or equal to 1.5 μm, and the maximum particle size D100 of the interface strengthening agent is greater than 0 and less than or equal to 4 μm.
[0041] Within this parameter range, smaller particle size increases the contact area with the silicon substrate, allowing for more thorough participation in the interfacial reaction during sintering and the formation of a continuous and uniform interfacial layer. This effectively reduces contact resistance and enhances the barrier properties against corrosive media. Simultaneously, strict control of the maximum particle size prevents additive particles from clogging the screen mesh, ensuring the printing quality of fine grid lines.
[0042] This application also provides a method for preparing a conductive paste, which can significantly improve the electrode's resistance to acetic acid, flux, and sodium chloride corrosion while ensuring high conductivity, good printability, and low additive content. Figure 1 A flowchart illustrating a method for preparing conductive paste according to an embodiment of this application is shown. Figure 1 As shown, the preparation method is as follows: S101: Mix 1 to 5 parts by weight of glass powder and interface strengthening agent, 87 to 92 parts by weight of silver conductive material and 7 to 10 parts by weight of organic carrier to obtain a premixed material.
[0043] For example, 1 to 5 parts by mass of glass powder and interface strengthening agent, 87 to 92 parts by mass of silver conductive material, and 7 to 10 parts by mass of organic carrier are weighed and thoroughly mixed in a mixing container to obtain a premixed material. In this step, the high content of silver conductive material ensures sufficient continuity of the subsequently formed conductive network, thereby achieving a low volume resistivity; the organic carrier, in the range of 7 to 10 parts, provides suitable viscosity and wettability, allowing the solid powders to adhere uniformly; the total addition of glass powder and interface strengthening agent is controlled at a low level of 1 to 3 parts, which helps reduce interference from non-conductive components on the contact between silver particles, while avoiding sintering defects caused by excessive addition. Premixing the above components uniformly ensures uniform stress on the material during subsequent three-roll rolling, improving dispersion efficiency. It should be noted that the mass parts mentioned here refer to the relative proportions of each component; in actual production, this proportion can be increased based on the total amount of material fed. Furthermore, the specific proportions of glass powder and interface strengthening agent can be adjusted according to actual needs within the above total range, but the sum of the two should not exceed 5 parts, otherwise it may affect the conductivity.
[0044] For example, the organic carrier provided in this application may include organic solvents, resins, and dispersants.
[0045] The organic solvents mentioned above can be selected from at least one of terpineol, diethylene glycol butyl ether, butyl carbitol, benzyl alcohol, and propylene glycol methyl ether acetate, and are used to adjust the rheological properties and drying rate of the slurry.
[0046] The resin can be selected from at least one of ethyl cellulose, acrylic resin, nitrocellulose, and polyvinyl butyral, and serves as a binder phase to provide slurry film-forming properties and electrode adhesion strength.
[0047] For example, the ethyl cellulose that may be used in this application includes, but is not limited to, at least one of STD 4, STD 7, and STD 10 from Dow ETHOCEL.
[0048] The dispersant mentioned above can be selected from at least one of polymeric dispersants (such as ammonium polyacrylate, polyvinylpyrrolidone, etc.) and surfactant dispersants (such as BYK-111, etc.).
[0049] The method for preparing the organic carrier in this application is as follows: Weigh appropriate amounts of resin and organic solvent and place them in a planetary mixer. After stirring evenly, add an appropriate amount of dispersant and mix evenly to form an organic carrier. It should be understood that the preparation method of the organic carrier is a conventional technique that does not require creative effort. Furthermore, the amount of components used in preparing the organic carrier is not the inventive point of this application and can be adjusted according to actual circumstances, and is not limited here.
[0050] S102: The premixed materials are dispersed evenly by three-roll milling to obtain a conductive slurry.
[0051] For example, in specific operations, it is usually necessary to control the roller gap and the number of rolling cycles so that the paste is repeatedly sheared and dispersed between the rollers until the silver powder, glass powder and interface strengthening agent are evenly distributed in the organic carrier and the paste fineness meets the requirements (for example, the fineness is generally no more than 15 micrometers when tested with a scraper fineness meter, but this application does not strictly limit this and can be adjusted according to actual printing needs). At this point, a conductive paste that can be directly used for screen printing is obtained.
[0052] Furthermore, the three-roll milling process utilizes the high shear force between the rollers to break up agglomerated particles, ensuring thorough wetting and dispersion of the components, thereby improving the uniformity of the paste and printing stability. It should be noted that in actual production, rolling parameters (e.g., roller gap, rotation speed, and number of cycles) should be adjusted according to the paste formulation and the equipment used to ensure effective dispersion without excessive heat generation leading to solvent evaporation. Uneven dispersion can result in broken grid lines during printing or excessively high electrode resistance after sintering, affecting battery performance.
[0053] This application also provides a method for preparing TOPCon cells, which can produce TOPCon cells with excellent resistance to acetic acid, flux corrosion and sodium chloride corrosion, and form optimal ohmic contacts through laser-assisted sintering, thereby ensuring the long-term reliability of the module. Figure 2 A flowchart illustrating the fabrication method of the TOPCon battery according to an embodiment of this application is shown. Figure 2 As shown, the preparation method is as follows: S201: The above-mentioned conductive paste is applied to the front electrode area of the TOPCon battery by screen printing. After printing, a fine grid pattern is formed, resulting in a battery cell with a wet paste grid on the surface.
[0054] Understandably, screen printing allows for precise control of the linewidth and thickness of the fine grid, which helps reduce light loss and ensure current collection efficiency. The height of the formed fine grid ranges from 3 to 7 μm, and the width ranges from 15 to 25 μm.
[0055] S202: TOPCon cells are formed by sequentially performing sintering, light injection, and laser-assisted sintering processes on the solar cells.
[0056] Understandably, the sintering process involves the volatilization of the organic carrier, the softening and flow of glass powder, and the etching of the passivation layer on the silicon wafer surface, while the silver powder sintersties to form a conductive network. Photoinjection improves the carrier lifetime of the silicon substrate; laser-assisted sintering promotes the formation of low-resistance ohmic contacts between silver and silicon by applying a reverse bias voltage combined with laser scanning. The laser power is 10–20 W, and the reverse bias voltage is 40–50 V.
[0057] It should be noted that the specific process parameters of the above-mentioned sintering, light injection and laser-assisted sintering (e.g. sintering temperature, light intensity and scanning speed) can be optimized according to the actual equipment and battery structure, and this application is not limited to specific values.
[0058] This application also provides a TOPCon battery, which is prepared by the above-described method for preparing a TOPCon battery.
[0059] To better demonstrate the effect of the conductive paste in this application, examples and comparative examples are presented herein.
[0060] Example 1 This example illustrates the preparation of glass powder.
[0061] The first step involves mixing the raw materials for preparing the glass powder according to the following mass percentages: 23 parts lead oxide, 9.6 parts bismuth trioxide, 3.1 parts silicon dioxide, 5.3 parts aluminum trioxide, 2.5 parts titanium dioxide, 51.5 parts boron trioxide, and 5 parts ferric oxide. The mixture is then placed in an alumina crucible. The crucible is then placed in a muffle furnace and held at 1100°C for 60 minutes to obtain molten glass.
[0062] The second step involves pouring the molten glass into a cold rolling mill for cold rolling to obtain cold-rolled glass sheets. These sheets are then ball-milled to produce glass powder with D50 ≤ 1.5 μm and D100 ≤ 4 μm.
[0063] Example 2 This example illustrates the preparation of glass powder.
[0064] The first step involves mixing the raw materials for preparing the glass powder according to the following mass percentages: 15 parts lead oxide, 29 parts bismuth trioxide, 2 parts silicon dioxide, 5 parts aluminum trioxide, 2 parts titanium dioxide, 43 parts boron trioxide, and 4 parts ferric oxide. The mixture is then placed in an alumina crucible. The crucible is then placed in a muffle furnace and held at 1100°C for 60 minutes to obtain molten glass.
[0065] The second step involves pouring the molten glass into a cold rolling mill for cold rolling to obtain cold-rolled glass sheets. These sheets are then ball-milled to produce glass powder with D50 ≤ 1.5 μm and D100 ≤ 4 μm.
[0066] Example 3 This example illustrates the preparation of glass powder.
[0067] The first step involves mixing the raw materials for preparing the glass powder by weight as follows: 20 parts lead oxide, 14 parts bismuth trioxide, 2.5 parts silicon dioxide, 11 parts aluminum trioxide, 1.5 parts titanium dioxide, 47.8 parts boron trioxide, and 3.2 parts ferric oxide. The mixture is then placed in an alumina crucible. The crucible is then placed in a muffle furnace and held at 1100°C for 60 minutes to obtain molten glass.
[0068] The second step involves pouring the molten glass into a cold rolling mill for cold rolling to obtain cold-rolled glass sheets. These sheets are then ball-milled to produce glass powder with D50 ≤ 1.5 μm and D100 ≤ 4 μm.
[0069] Example 4 This example illustrates the preparation of glass powder.
[0070] The first step involves mixing the raw materials for preparing the glass powder by weight as follows: 22.3 parts lead oxide, 9.3 parts bismuth trioxide, 2.4 parts silicon dioxide, 10.2 parts aluminum trioxide, 1.6 parts titanium dioxide, 48 parts boron trioxide, 1.6 parts ferric oxide, and 4.6 parts tungsten trioxide. The mixture is then placed in an alumina crucible. The crucible is then placed in a muffle furnace and held at 1100°C for 60 minutes to obtain molten glass.
[0071] The second step involves pouring the molten glass into a cold rolling mill for cold rolling to obtain cold-rolled glass sheets. These sheets are then ball-milled to produce glass powder with D50 ≤ 1.5 μm and D100 ≤ 4 μm.
[0072] Example 5 This example illustrates the preparation of glass powder.
[0073] The first step involves mixing the raw materials for preparing the glass powder by weight as follows: 22.6 parts lead oxide, 9.4 parts bismuth trioxide, 2.5 parts silicon dioxide, 10.3 parts aluminum trioxide, 1.6 parts titanium dioxide, 48.6 parts boron trioxide, 1.6 parts ferric oxide, and 3.4 parts cobalt trioxide. The mixture is then placed in an alumina crucible. The crucible is then placed in a muffle furnace and held at 1100°C for 60 minutes to obtain molten glass.
[0074] The second step involves pouring the molten glass into a cold rolling mill for cold rolling to obtain cold-rolled glass sheets. These sheets are then ball-milled to produce glass powder with D50 ≤ 1.5 μm and D100 ≤ 4 μm.
[0075] Comparative Example 1 This comparative example is for the preparation of glass powder.
[0076] The first step involves mixing the raw materials for preparing the glass powder by weight as follows: 30 parts lead oxide, 3.3 parts silicon dioxide, 5.5 parts aluminum oxide, 2.6 parts titanium dioxide, 53.4 parts boron trioxide, and 5.2 parts ferric oxide. The mixture is then placed in an alumina crucible. The crucible is then placed in a muffle furnace and held at 1100°C for 60 minutes to obtain molten glass.
[0077] The second step involves pouring the molten glass into a cold rolling mill for cold rolling to obtain cold-rolled glass sheets. These sheets are then ball-milled to produce glass powder with D50 ≤ 1.5 μm and D100 ≤ 4 μm.
[0078] Comparative Example 2 This comparative example is for the preparation of glass powder.
[0079] The first step involves mixing the raw materials for preparing the glass powder by weight as follows: 46.1 parts bismuth trioxide, 2.5 parts silicon dioxide, 4.2 parts aluminum oxide, 2 parts titanium dioxide, 41.3 parts boron trioxide, and 3.9 parts ferric oxide. The mixture is then placed in an alumina crucible. The crucible is then placed in a muffle furnace and held at 1100°C for 60 minutes to obtain molten glass.
[0080] The second step involves pouring the molten glass into a cold rolling mill for cold rolling to obtain cold-rolled glass sheets. These sheets are then ball-milled to produce glass powder with D50 ≤ 1.5 μm and D100 ≤ 4 μm.
[0081] Comparative Example 3 This comparative example is for the preparation of glass powder.
[0082] The first step involves mixing the raw materials for preparing the glass powder by weight as follows: 23 parts lead oxide, 10 parts bismuth trioxide, 5 parts silicon dioxide, 5.3 parts aluminum trioxide, 52 parts boron trioxide, and 4.7 parts ferric oxide. The mixture is then placed in an alumina crucible. The crucible is then placed in a muffle furnace and held at 1100°C for 60 minutes to obtain molten glass.
[0083] The second step involves pouring the molten glass into a cold rolling mill for cold rolling to obtain cold-rolled glass sheets. These sheets are then ball-milled to produce glass powder with D50 ≤ 1.5 μm and D100 ≤ 4 μm.
[0084] Example 6 This example illustrates the preparation of a conductive paste.
[0085] First, weigh 3 parts of ethyl cellulose (Dow ETHOCEL STD 7) and 5 parts of terpineol and place them in a planetary mixer. Stir at 60°C for 2 hours, then add 0.5 parts of dispersant BYK-111 and mix thoroughly to form an organic carrier. Next, mix 2 parts of the glass powder obtained in Example 1, 0.5 parts of alumina powder as an interface strengthening agent, 89.50 parts of silver powder with an average particle size D50 of 0.5~2μm, and 8.50 parts of the organic carrier. Stir at a planetary mixer speed of 1200 rpm for 1 hour to obtain a premixed material.
[0086] The second step is to disperse the premixed materials evenly through a three-roll mill to obtain a conductive slurry.
[0087] The roller gap is 20μm, the roller speed ratio is 1:3:9, and the rolling process is 5 passes.
[0088] Example 7 This example illustrates the preparation of a conductive paste.
[0089] The first step involved weighing 3 parts of ethyl cellulose (Dow ETHOCEL STD 7) and 5 parts of terpineol and placing them in a planetary mixer. The mixture was stirred at 60°C for 2 hours, and then 0.5 parts of dispersant BYK-111 were added and mixed thoroughly to form an organic carrier. 2 parts of the glass powder obtained in Example 2, 0.5 parts of alumina powder as an interface strengthening agent, 89.50 parts of silver powder with an average particle size D50 of 0.5~2μm, and 8.50 parts of the organic carrier were mixed and stirred at a planetary mixer speed of 1200 rpm for 1 hour to obtain a premixed material.
[0090] The second step is to disperse the premixed materials evenly through a three-roll mill to obtain a conductive slurry.
[0091] The roller gap is 20μm, the roller speed ratio is 1:3:9, and the rolling process is 5 passes.
[0092] Example 8 This example illustrates the preparation of a conductive paste.
[0093] First, weigh 3 parts of ethyl cellulose (Dow ETHOCEL STD 7) and 5 parts of terpineol and place them in a planetary mixer. Stir at 60°C for 2 hours, then add 0.5 parts of dispersant BYK-111 and mix thoroughly to form an organic carrier. Use 2 parts of the glass powder obtained in Example 3, 0.5 parts of aluminum-silicon alloy powder as an interface strengthening agent, 89.50 parts of silver powder with an average particle size D50 of 0.5~2μm, and 8.50 parts of the organic carrier as a mixture. Stir at a planetary mixer speed of 1200 rpm for 1 hour to obtain a premixed material.
[0094] The second step is to disperse the premixed materials evenly through a three-roll mill to obtain a conductive slurry.
[0095] The roller gap is 20μm, the roller speed ratio is 1:3:9, and the rolling process is 5 passes.
[0096] Example 9 This example illustrates the preparation of a conductive paste.
[0097] The first step involved weighing 3 parts of ethyl cellulose (Dow ETHOCEL STD 7) and 5 parts of terpineol and placing them in a planetary mixer. The mixture was stirred at 60°C for 2 hours, and then 0.5 parts of dispersant BYK-111 were added and mixed thoroughly to form an organic carrier. 2 parts of the glass powder obtained in Example 4, 0.25 parts of alumina powder, and 0.25 parts of aluminum-silicon alloy powder were used as interface strengthening agents. 89.50 parts of silver powder with an average particle size D50 of 0.5~2 μm and 8.50 parts of the organic carrier were mixed and stirred at a planetary mixer speed of 1200 rpm for 1 hour to obtain a premixed material.
[0098] The second step involves uniformly dispersing the premixed materials through a three-roll mill to obtain a conductive slurry. The roller gap is 20 μm, the roller speed ratio is 1:3:9, and the milling process is performed five times.
[0099] Example 10 This example illustrates the preparation of a conductive paste.
[0100] First, weigh 3 parts of ethyl cellulose (Dow ETHOCEL STD 7) and 5 parts of terpineol and place them in a planetary mixer. Stir at 60°C for 2 hours, then add 0.5 parts of dispersant BYK-111 and mix thoroughly to form an organic carrier. Then, mix 2 parts of the glass powder obtained in Example 5, 0.5 parts of alumina powder as an interface strengthening agent, 89.50 parts of silver powder with an average particle size D50 of 0.5~2μm, and 8.50 parts of the organic carrier. Stir at a planetary mixer speed of 1200 rpm for 1 hour to obtain a premixed material.
[0101] The second step is to disperse the premixed materials evenly through a three-roll mill to obtain a conductive slurry.
[0102] The roller gap is 20μm, the roller speed ratio is 1:3:9, and the rolling process is 5 passes.
[0103] Comparative Example 4 This comparative example is for the preparation of conductive paste.
[0104] First, weigh 3 parts of ethyl cellulose (Dow ETHOCEL STD 7) and 5 parts of terpineol and place them in a planetary mixer. Stir at 60°C for 2 hours, then add 0.5 parts of dispersant BYK-111 and mix thoroughly to form an organic carrier. Then, mix 2 parts of the glass powder obtained in Comparative Example 1, 0.5 parts of alumina powder as an interface strengthening agent, 89.50 parts of silver powder with an average particle size D50 of 0.5~2μm, and 8.50 parts of the organic carrier. Stir at a planetary mixer speed of 1200 rpm for 1 hour to obtain a premix.
[0105] The second step is to disperse the premixed materials evenly through a three-roll mill to obtain a conductive slurry.
[0106] The roller gap is 20μm, the roller speed ratio is 1:3:9, and the rolling process is 5 passes.
[0107] Comparative Example 5 This comparative example is for the preparation of conductive paste.
[0108] First, weigh 3 parts of ethyl cellulose (Dow ETHOCEL STD 7) and 5 parts of terpineol and place them in a planetary mixer. Stir at 60°C for 2 hours, then add 0.5 parts of dispersant BYK-111 and mix thoroughly to form an organic carrier. Then, mix 2 parts of the glass powder obtained in Comparative Example 2, 0.5 parts of alumina powder as an interface strengthening agent, 89.50 parts of silver powder with an average particle size D50 of 0.5~2μm, and 8.50 parts of the organic carrier. Stir at a planetary mixer speed of 1200 rpm for 1 hour to obtain a premix.
[0109] The second step is to disperse the premixed materials evenly through a three-roll mill to obtain a conductive slurry.
[0110] The roller gap is 20μm, the roller speed ratio is 1:3:9, and the rolling process is 5 passes.
[0111] Comparative Example 6 This comparative example is for the preparation of conductive paste.
[0112] First, weigh 3 parts of ethyl cellulose (Dow ETHOCEL STD 7) and 5 parts of terpineol and place them in a planetary mixer. Stir at 60°C for 2 hours, then add 0.5 parts of dispersant BYK-111 and mix thoroughly to form an organic carrier. Then, mix 2 parts of the glass powder obtained in Comparative Example 3, 0.5 parts of alumina powder as an interface strengthening agent, 89.50 parts of silver powder with an average particle size D50 of 0.5~2μm, and 8.50 parts of the organic carrier. Stir at a planetary mixer speed of 1200 rpm for 1 hour to obtain a premixed material.
[0113] The second step is to disperse the premixed materials evenly through a three-roll mill to obtain a conductive slurry.
[0114] The roller gap is 20μm, the roller speed ratio is 1:3:9, and the rolling process is 5 passes.
[0115] Based on this, the conductive pastes obtained in Examples 6 to 10 and Comparative Examples 4 to 6 were respectively used to fabricate solar cells, as follows: The first step involves applying the aforementioned conductive paste to the front electrode area of the TOPCon battery using screen printing, resulting in a battery cell with a fine grid of wet paste on its surface. The height of this fine grid is 3-7 μm, and its width is 15-25 μm.
[0116] The second step involves sequentially sintering, light injection, and laser-assisted sintering of the battery cells, applying a reverse bias voltage, and then laser scanning the front side of the battery to form a TOPCon battery.
[0117] The sintering process parameters are as follows: peak sintering temperature of 750℃, sintering belt speed of 19.0 m / min, and high-temperature holding time of 2 s. The light injection process parameters are as follows: injection light intensity of 30 sun, processing temperature of 500℃, and processing time of 10 s. The auxiliary sintering process parameters are as follows: laser power of 15W and reverse bias voltage of 45V.
[0118] Based on this, acetic acid experiments, flux experiments, and NaCl corrosion experiments were conducted on the prepared TOPCon batteries to verify the influence of the conductive pastes obtained in Examples 6 to 10 and Comparative Examples 4 to 6 on the performance of the TOPCon batteries.
[0119] Test Example 1 This test example illustrates the testing procedure for acetic acid.
[0120] A 10% acetic acid solution was placed in a sealed box. The solar cells were placed vertically above the acetic acid solution, maintaining equal spacing between them. The box was then placed in an 85°C oven for 6 hours. After removing the solar cells, they were cooled to room temperature. The efficiency Eta before and after the acetic acid experiment was measured, and the efficiency degradation rate was calculated as: (Eta before experiment - Eta after experiment) / Eta before experiment × 100%.
[0121] Test Example 2 This test example illustrates the testing process for flux experiments.
[0122] Apply 3 drops of flux to the surface of the solar cell using a dropper, repeating this process at 2-4 locations. Let the solar cell lie flat and stand for 20 minutes to air dry naturally. After drying, place it in a 150℃ oven and bake for 30 minutes. After cooling, test the EL change. The less the EL change, the better the resistance to flux corrosion.
[0123] Test Example 3 This test example demonstrates the process of NaCl corrosion testing.
[0124] Stack the battery cells together vertically, and drop 2 ml of 2% NaCl solution vertically from the top. After standing vertically for 24 hours, pass them through a drying oven at 400℃. Test the efficiency Eta before and after the experiment, and calculate the efficiency decay rate: (Eta after the experiment - Eta before the experiment) / Eta before the experiment × 100%.
[0125] Table 1 shows the acetic acid test results of solar cells made from the conductive pastes obtained in Examples 6 to 10 and Comparative Examples 4 to 6 of this application.
[0126] Table 1
[0127] Table 2 shows the NaCl corrosion test results of solar cells made from the conductive pastes obtained in Examples 6 to 10 and Comparative Examples 4 to 6 of this application.
[0128] Table 2
[0129] Figures 3 to 10 Images of electroluminescence tests acquired after flux experiments of solar cells made from the conductive pastes obtained in Examples 6 to 10 and Comparative Examples 4 to 6 of this application are shown in sequence.
[0130] 1. According to the acetic acid test results in Table 1, the efficiency decay rate of Examples 6 to 10 of this application is 10.7% to 13.5%, which is much lower than that of Comparative Examples 4 to 6 (20.9% to 25.6%).
[0131] Comparative Examples 4 and 5 contained only lead oxide or only bismuth oxide, respectively, while the examples contained both lead oxide and bismuth oxide. This is because lead oxide and bismuth oxide can form a complementary dual network in the glass network: the high charge density of bismuth ions enhances the bonding strength with oxygen ions, while lead ions provide necessary charge compensation, thereby reducing the number of non-bridging oxygen atoms, making the glass network more complete and dense, and significantly improving the chemical stability of the glass. Furthermore, Comparative Example 6, without the addition of titanium dioxide, showed significantly worse resistance to acetic acid corrosion than the examples with added titanium dioxide. When ferric oxide and titanium dioxide coexist, iron and titanium enhance network connectivity by forming iron-oxygen-titanium bonds. Iron ions act as charge compensators, and titanium ions act as network reinforcing agents; both synergistically improve the integrity and stability of the glass network. Therefore, the glass compositions in the examples containing both lead oxide / bismuth oxide and ferric oxide / titanium dioxide are more effectively resistant to acetic acid corrosion, thereby reducing efficiency degradation.
[0132] 2. According to the sodium chloride corrosion test results in Table 2, the efficiency decay rate of Examples 6 to 10 of this application is 0.2% to 0.5%, which is significantly lower than the 1.0% to 1.9% of Comparative Examples 4 to 6. Consistent with the acetic acid test results, Comparative Examples 4 and 5, which contain only lead oxide or only bismuth oxide, and Comparative Example 6, which does not contain titanium dioxide, all exhibit significantly weaker resistance to sodium chloride corrosion than the examples containing both lead oxide / bismuth oxide and ferric oxide / titanium dioxide. The above mechanism also applies to the sodium chloride corrosion environment: the lead-bismuth dual network and the iron-titanium synergistic reinforcement make the glass phase more compact, effectively blocking the chloride ion penetration pathway, thereby protecting the electrode and silicon substrate from corrosion. This further verifies the effectiveness of the glass composition defined in this application in improving the salt spray corrosion resistance of the battery.
[0133] 3. For example Figures 3 to 10 As shown, the images corresponding to Embodiments 6 to 10 of this application have high overall brightness and uniform light emission, with no obvious dark spots, blackened areas or dark lines near the grid lines, indicating that the flux has not caused significant corrosion to the battery and the electrode-battery interface remains intact.
[0134] The images corresponding to Comparative Examples 4 to 6 of this application show varying degrees of reduced brightness, localized blackening, or patchy dark areas. The dark areas in Comparative Examples 4 and 5 are more pronounced, while the dark area in Comparative Example 6 is slightly less severe, but still significantly worse than in the embodiments, indicating that the electrodes of these three battery groups are significantly eroded by flux.
[0135] As can be seen, the embodiments of this application simultaneously contain lead oxide and bismuth trioxide, which can form a stable and complementary glass network structure. Combined with the synergistic effect of titanium dioxide and ferric oxide, the glass layer becomes denser, effectively blocking flux penetration. In contrast, Comparative Example 4 contains only lead oxide, and Comparative Example 5 contains only bismuth trioxide; their glass network structures are incomplete, resulting in poor corrosion resistance. Comparative Example 6, without the addition of titanium dioxide, has a weak glass network connection and is also easily corroded by flux.
[0136] The above description is merely a specific embodiment of this application. Obviously, various modifications and combinations can be made without departing from the spirit and scope of this application. Accordingly, this specification and accompanying drawings are merely exemplary descriptions of this application as defined by the appended claims, and are considered to cover any and all modifications, variations, combinations, or equivalents within the scope of this application. Clearly, those skilled in the art can make various alterations and modifications to this application without departing from the spirit and scope of this application. Thus, if these modifications and modifications of this application fall within the scope of the claims of this application and their equivalents, the intent of this application includes these modifications and modifications. Any changes or substitutions that can be easily conceived by those skilled in the art within the scope of the technology disclosed in this application should be included within the protection scope of this application. Therefore, the protection scope of this application should be determined by the protection scope of the stated claims. It should also be noted that in the apparatus and method of this application, the components or steps can be disassembled and / or recombined. These disassemblies and / or recombinations should be considered equivalent solutions of this application. The above description of the disclosed aspects is provided to enable any person skilled in the art to make or use this application. Various modifications to these aspects will be readily apparent to those skilled in the art, and the general principles defined herein can be applied to other aspects without departing from the scope of this application. Therefore, this application is not intended to be limited to the aspects shown herein, but rather to be applied within the widest scope consistent with the principles and novel features disclosed herein. The above description has been given for purposes of illustration and description. Furthermore, this description is not intended to limit the embodiments of this application to the forms disclosed herein. Although several exemplary aspects and embodiments have been discussed above, those skilled in the art will recognize certain variations, modifications, alterations, additions, and sub-combinations thereof.
Claims
1. A conductive paste, characterized in that, The raw materials for the conductive paste include: The conductive paste contains silver conductive material, an organic carrier, glass powder, and an interface strengthening agent. Based on the mass fraction of the conductive paste, the silver conductive material comprises 87 to 92 parts, the organic carrier comprises 7 to 10 parts, and the glass powder and interface strengthening agent comprise 1 to 5 parts. The glass powder comprises a lead-bismuth oxide component, an iron-titanium oxide component, and an auxiliary glass-forming component. Based on the mass fractions of the glass powder, the lead-bismuth oxide component comprises 30 to 50 parts, the iron-titanium oxide component comprises 2 to 10 parts, and the auxiliary glass-forming component comprises 40 to 68 parts.
2. The conductive paste according to claim 1, characterized in that, The lead-bismuth oxide component includes lead oxide and bismuth oxide, and the iron-titanium oxide component includes iron oxide and titanium oxide.
3. The conductive paste according to claim 2, characterized in that, Based on the mass fractions of the glass powder, the lead oxide comprises 10 to 40 parts, the bismuth oxide comprises 5 to 30 parts, the iron oxide comprises 1 to 9 parts, and the titanium oxide comprises 1 to 5 parts.
4. The conductive paste according to claim 1, characterized in that, The auxiliary glass-forming component includes a primary glass-forming component and a secondary glass phase component; The main glass-forming components include boron oxide, silicon oxide, and aluminum oxide. Based on the mass fractions of the glass powder, the boron oxide comprises 30 to 60 parts, the silicon oxide comprises 0.5 to 5 parts, and the aluminum oxide comprises 5 to 15 parts; the minor glass phase components comprise 0 to 5 parts.
5. The conductive paste according to claim 1, characterized in that, Based on the mass fraction of the conductive paste, the glass powder comprises 1 to 4 parts, and the interface strengthening agent comprises more than 0 and less than or equal to 1 part.
6. The conductive paste according to claim 5, characterized in that, The interface strengthening agent includes one or more of aluminum powder, silicon powder, aluminum-silicon alloy powder, and alumina powder.
7. The conductive paste according to any one of claims 1 to 6, characterized in that, The average particle size D50 of the silver conductive material is 0.5~2μm, and the maximum particle size D100 of the silver conductive material is greater than 0 and less than or equal to 4μm.
8. The conductive paste according to any one of claims 1 to 6, characterized in that, The average particle size D50 of the glass powder is greater than 0 and less than or equal to 1.5 μm, and the maximum particle size D100 of the glass powder is greater than 0 and less than or equal to 4 μm.
9. The conductive paste according to any one of claims 1 to 6, characterized in that, The average particle size D50 of the interface strengthening agent is greater than 0 and less than or equal to 1.5 μm, and the maximum particle size D100 of the interface strengthening agent is greater than 0 and less than or equal to 4 μm.
10. A method for preparing the conductive paste according to any one of claims 1 to 9, characterized in that, include: A premixed material is obtained by mixing 1 to 5 parts by weight of glass powder and interface strengthening agent, 87 to 92 parts by weight of silver conductive material and 7 to 10 parts by weight of organic carrier. The premixed materials are dispersed evenly by three-roll milling to obtain a conductive slurry.
11. A method for preparing a TOPCon battery, characterized in that, include: The conductive paste described in any one of claims 1 to 9 is applied to the front electrode area of the TOPCon battery by screen printing, and a fine grid pattern is formed after printing to obtain a battery cell with a wet paste grid on the surface. The battery cells are sequentially subjected to sintering, light injection, and laser-assisted sintering to form TOPCon batteries.
12. A TOPCon battery, characterized in that, include: It is prepared by the method of TOPCon battery preparation according to claim 11.